2013
DOI: 10.1097/aog.0b013e31827e7fd9
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Compared With Delayed Oxytocin After Amniotomy Labor Induction in Parous Women

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…We believe that our sample size is adequately powered to test our hypothesis on the independent role of phIGFBP‐1 in predicting successful labour induction, using multivariable logistic regression analysis as the statistical tool. Our study population of nulliparas alone is apt, as multiparas undergoing labour induction have a reported 97% vaginal delivery rate and a speedy induction process, with about 96% delivering vaginally within 12 hours of amniotomy to induce labour, rendering predictor systems clinically superfluous for multiparas. We controlled for many known confounding factors in our models.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that our sample size is adequately powered to test our hypothesis on the independent role of phIGFBP‐1 in predicting successful labour induction, using multivariable logistic regression analysis as the statistical tool. Our study population of nulliparas alone is apt, as multiparas undergoing labour induction have a reported 97% vaginal delivery rate and a speedy induction process, with about 96% delivering vaginally within 12 hours of amniotomy to induce labour, rendering predictor systems clinically superfluous for multiparas. We controlled for many known confounding factors in our models.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies established there is no real difference in clinical outcomes between oxytocin administration with ruptured or intact membranes (24). In a 2013 RTC Tan et al concluded that the choice between the two options should take into account local resources and the woman preference (25). Regarding oxytocin administration, the majority of midwives use it following specific protocols (87.8%), always giving it through an infusion pump (65.4%) and monitoring foetal heart rate and contractile activity continuously (96.5%) (table III).…”
Section: Discussionmentioning
confidence: 99%
“…We found no significant changes in child death among all treatment regimens. Previous studies reported that pulsatile or delayed OXT regimens were associated with longer labor and more chances of child death [ 9 , 24 ]. Previous studies reported such adverse effects of pulsatile OXT regimen because of large sample size [ 25 ] or lack of proper knowledge or exposure regarding administration of dosage forms [ 26 ].…”
Section: Discussionmentioning
confidence: 99%